Profil Pemecahan Masalah Matematika Siswa Ditinjau dari Gaya Kognitif Reflektif dan Impulsif - Imam Muhtadi Azhil (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2017)
This research aims to explain the ability of problem-solving between reflective cognitive and impulsive cognitive students. The subject of this research is students of class VII C SMP Al-Hikmah Surabaya. Subject chose based on a test of cognitive style, one student of reflective cognitive style and one student of impulsive cognitive style. The instrument uses a test of the MFF (Matching Familiar Figures) and tests the ability to problem-solving of ratio. The subject of reflective cognitive style can retell the problems that exist in the problem, said, write down the steps used in the settlement of a matter, carry out all settlement plan as a whole and coherent, and provide settlement solutions at the end of time. The subject of impulsive cognitive style, the average can tell, mention, write on some matter, of course, does not implement the settlement plan, not coherent, and settlement in a hurry.